Implementation of Total Quality Management to Realize Quality Education at State X Elementary School Cirebon, West Java - Dariyo, Agoes (Cakrawala : Jurnal Kajian Manajemen Pendidikan Islam dan Studi Sosial, 2025)
The general problem faced by state primary education is the low quality of education which has a negative impact on the low competency of its graduates, so that they unable to compete with other graduate to continue state secondary education. Total Quality Management (TQM) is integrated quality management that can answer the problem of low quality of education, meaning that implementing TQM is the right solution to realizing quality education in primary schools. TQM has long been applied to improve the quality of production of goods or services in business companies that are oriented towards customers satisfaction, but now TQM has been widely applied to overcome the problem of low quality education, such as in elementary schools. This research aims to find out an overview of the implementation of Total Quality Management to realize quality education at the XY Cirebon State Elementary School, West Java. The data collection techniques uses the Total Quality Management questionnaire and the Education Quality questionnaire. The TQM concept uses the concept of modern management theory from George Robert Terry (planning, organizing, actuacting, and controlling) and the quality of education uses the concept of Unicef. The sampling technique is simple random sampling, The number of research participants uses 22 people (teachers and educational staff). The data analysis technique uses simple descriptive statistical tests. The research results have shown that the implementation of TQM can improve the quality of education at XY Cirebon Elementary School, West Java.